An Immunologic Basis for Placental Insufficiency in Fetal Growth Restriction - Greer, Laura G.; Ziadie, Mandolin S.; Casey, Brian M.; Rogers, Beverly B.; McIntire, Donald D.; Leveno, Kenneth J. (American Journal of Perinatology, 2012)
Objective We sought to determine whether chronic villitis, an immunologic disease of the placenta, was related to fetal growth restriction.Methods Beginning in October 1999, a protocol was instituted that required placentas of high-risk births be submitted for standardized histological examination. Chronic villitis was diagnosed when a lymphohistiocytic infiltrate involving placental villi was present and was graded according to the extent and location of the infiltrate. Fetal growth restriction was defined as weight less than 3rd, 5th, and 10th percentiles. Placental hypoplasia was defined as weight less than 10th percentile.Results In the 10,204 placental examinations that were performed, low-grade and high-grade chronic villitis was associated with hypoplastic placentas and fetal growth restriction. Infants with placentas with low-grade and high-grade chronic villitis were more likely to require cesarean delivery for nonreassuring fetal heart rate compared with controls (27% and 25% versus 21%; p < 0.05). Fetal acidemia (umbilical artery pH < 7.0) was associated with high-grade chronic villitis compared with controls (4% versus 2%; p < 0.05).Conclusion Chronic villitis was associated with anatomic and functional placental insufficiency manifested as placental hypoplasia, growth restriction, increased risk of cesarean for nonreassuring fetal heart rate, and fetal acidemia. These findings support an immunologic basis for fetal growth restriction.
Keywords: growth restriction; chronic villitis; placental hypoplasia; placental insufficiency